(untitled) (American Journal of Islam and Society, 2003)
Political Development: An Islamic Perspective is divided into two broad parts: the conceptual foundations of political development and its case studies. Part One contains seven chapters that deal with the conceptual foundations of political development, thereby signifying the importance of clarifying the concept so that an Islamic alternative to political development can be found. Part Two contains three chapters, each a case study of the political development experience in Bangladesh, Malaysia, and Sudan. Khurshid Ahmad, a central figure in the London-based Islamic Foundation, provides the much-needed position from which an Islamic perspective on political development should begin. His chapter, "Islamic Approach to Development," outlines the philosophical foundations of an Islamic approach to development and the goals of a development policy. He begins by uncovering the flaws of western thinking on development, which have resulted in what he calls "de-development." The West’s various development strategies are actually designed so that the developed countries can exploit the developing countries. Tn terms of development’s philosophical foundations, Ahmad empha sizes tawhid (God’s unity and sovereignty), rububiyah (the divine arrangements for nourishing, sustaining, and directing things toward their perfection), khilafah (human beings’ role as God’s vicegerent on Earth), and tazkiyah (purification plus growth). Hence, Islam’s position takes into account humanity’s role vis-a-vis its Creator and fellow human beings. The objectives of development transcend this world, for they also have an eye on the Hereafter ...